PENDIDIKAN GIZI MENGGUNAKAN MEDIA EXPLODING BOX TERHADAP PENGETAHUAN TENTANG SAYUR DAN BUAH PADA ANAK SEKOLAH DASAR - Osman Syarief; Futri Handayani; Widartika Widartika; Judiono Judiono; Gurid Mulyo (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Vegetables and fruits are very important for daily consumption, including school-age children, the consumption of vegetables and fruit in school-age children can be influenced by several factors, one of which is knowledge of the frequency of consumption of vegetables and fruit. Knowledge and behavior of the frequency of consumption of vegetables and fruits can be influenced one of them by the existence of nutritional education using exploding boxes as a medium of nutrition education. The purpose of this study is to determine the Effect of Nutrition Education Using Media Exploding Box Against Knowledge and Behavior Frequency of Consumption of Vegetables and Fruits in Children Citamiang 1 Primary School, Purwakarta Regency. The research design used was a quasi experimental study with a pre-test and post-test control group design with a sample size of 38 people, taken using systematic random sampling technique. Data collection includes general data on age, sex, pre and post knowledge related to vegetables and fruits before and after nutrition education for intervention and control groups and interviews with FFQ (Food Frequency Quantitative) consumption of vegetables and fruits. The results showed there was an influence of nutrition education using media exploding boxes on student knowledge with the results of p value 0.003 <α (0.05). The increase in the mean score of the intervention group was greater than the control group. There is an influence of nutrition education using the media exploding box on knowledge related to vegetables and fruits in the intervention group with a p value of 0,000 <α (0.05) Conclusion: Nutrition education or nutrition education for school children can use the media exploding box as a media for nutrition education